(untitled) (International Current Pharmaceutical Journal, 2013)
In the present investigation, the saponins rich fraction of roots of Cassia auriculata L. was evaluated for antimicrobial activity against P. vesicularis, Streptococcus faecalis, Aeromonas hydrophilia, Salmonella typhae, Staphylococcus cohni, Serratia ficaria and E. coli at concentration of 12.5 mg/ml, 25 mg/ml, 37.5 mg/ml and 50 mg/ml. Antimicrobial activity of Cassia auriculata L. was carried out by well diffusion method. At maximum conc. i.e. 50mg/ml, antimicrobial effect of Saponin rich extract can be arranged in sequence of - P. vesicularis > Serratia ficaria > Streptococcus cohni > Aeromonas hydrophilic> Salmonella typhae > Sterptococcus faecalis > E. coli. The results indicate the saponins rich fraction of roots of Cassia auriculata L. might be exploited as natural drug for the treatment of several infectious diseases caused by these organisms. Cassia auriculata L. was observed to have antibacterial activity and can be used for medicinal purposes. DOI: http://dx.doi.org/10.3329/icpj.v2i4.14056 International Current Pharmaceutical Journal, March 2013, 2(4): 85-87